Correlation and Path Analysis for Yield and its Phenological, Physiological, Morphological and Biochemical Traits under Salinity Stress in Chickpea (Cicer arietinum L.) - Tutlani, Aman; Kumar, Rajneesh; Banshidhar; Kumari, Smita; Chouhan, Shambhu (International Journal of Bio-resource and Stress Management, 2023)
The investigation was carried out during rabi season (November–April) of 2020–2021 in the polyhouse, Department of Genetics and Plant Breeding, Lovely Professional University, Phagwara, Punjab, India. CRD (Completely Randomize Design) were used in 3 replications with the objective to assess the performance of 20 chickpea genotypes under salinity stress conditions in order to identify genotypes that demonstrate greater tolerance to these conditions. To induce the salinity stress, NaCl salts were administer in two split doses of 120 mM during sowing and at 15 DAS. The study evaluated a range of parameters, including phenological, physiological, morphological, biochemical, and yield parameters, to examine the impact of salt stress on genotypes that exhibit varying levels of tolerance. Total proline content increment is due to increase of stress related proteins during the salinity. The yield parameters increase in non-saline conditions whereas in stress conditions, yield will get reduce. The findings revealed an increase in the total Proline content due to the production of stress-related proteins during salinity stress; however, yield parameters were negatively affected under stress conditions, with the most significant decrease observed in the 120 mM NaCl treatment group compared to the control group. ICC5439 and GNG 1581 emerged as highly tolerant chickpea genotypes under salinity stress conditions, while ICC 6050, ICC 251, ICC 252, and ICC 262 exhibited medium tolerance. In contrast, ICC253, ICC 247, and ICC 249 were found to be highly susceptible genotypes, with the remaining genotypes showing minimal tolerance and sensitivity to salinity stress.